Transformation of the concepts and practice of total pain and total care: 30 years of Danish hospices - Timm, Helle (Frontiers in Sociology, 2023)
The concept of total pain endeavors to encompass central aspects of suffering in relation to severe disease, death and dying. Dame Cicely Saunders introduced the concept in the early 1960s in relation to care for the terminally ill and dying patients with cancer. An examination of Danish palliative care, particularly Danish hospice care, indicates that total pain continues to be a relevant concept today. To further explore the current relevance of total pain the study examines its underlying ontology, epistemology and methodology. The study also addresses how the understanding and practice of total pain theory has developed throughout its history, in addition to how the understanding of concepts and practices is constantly being negotiated, shaped and transformed in relation to changes in society and by individuals, groups and organizations. The first of 21 hospices in Denmark opened in 1992 and they represent a case in point for exploring the transformation of total pain and total care since then. The empirical data, which are based on materials relevant to the history of the hospice movement and practice in Denmark, include national policy documents, local yearbooks, mapping, research, documentation of practice, interviews and on-going dialogue with management and staff at Danish hospices over the last 25 years. The study, which takes an abductive analytical approach, draws on my own experiences and empirical data, in addition to the empirical and theoretical research of others but also gains inspiration from a theoretical institutional logic perspective. Research shows that there are three main co-existing and interrelated institutional logics in the history of Danish hospices: care, medicine and governance. Based on inspiration from sociological and philosophical palliative care research and data on the development of Danish hospices, this study demonstrates how the concepts and practices of total pain and total care have been transformed in the compromises made due to the co-existence of these competing logics.